The willingness to pay for African wormwood and Cancer bush capsules among youths in Mbombela, South Africa - Nobuhle P. Nsibanyoni; Chiedza Z. Tsvakirai; Tshehla Makgopa (AOSIS, 2023)
Background: The demand for African wormwood and Cancer bush has surged as modern healthcare products have provided limited solutions for the ailments they treat. Moreover, there has been an increase in younger consumers of these medicinal plants, who expect lower-priced products which have a 'polished look' that is similar to over-the-counter medicinal products. Aim: This study investigates the need to introduce lower-priced capsules to meet these changes in consumer product preferences. Setting: The study was conducted in the city of Mbombela. This is a city that has a rich heritage in indigenous medicinal plant use but has the absence of a large informal market for their sale. Methods: A willingness-to-pay analysis was conducted. It utilised survey data that was collected from 105 university students. Results: The study found that there were two market segments split with a ratio of about 3:1 between those willing to pay a price similar to a conventional product in the lower price range and those not willing. However, the market potential for introducing a lower-priced product was only found in the Cancer bush market, where respondents were willing to procure the product at a discounted price, as opposed to the African wormwood market, where some respondents were not willing to part with any money at all. Conclusion: The study concludes that there is potential for lucrative market diversification if the industry introduces lower-priced capsules for Cancer bush. Contribution: The study provides insights into the possible areas of market development in the African indigenous medicines market.